The diffusion of digital skills across EU regions: Structural drivers and polarization dynamics - Serenella Caravella; Valeria Cirillo; Francesco Crespi; Dario Guarascio; Mirko Menghini (Global Labor Organization (GLO), 2022)
The digital transformation is an important driver of long-run productivity growth and, as such, it has the potential to promote a more inclusive and sustainable growth. However, digital capabilities, crucial to develop and govern new digital technologies, are unevenly distributed across European regions increasing the risk of divergence and polarization. By taking advantage of a set of original indicators capturing the level of digital skills in the regional workforce, this work analyzes the factors shaping the process of digital skill accumulation in the EU over the period 2011-2018. Relying on transition probability matrices and dynamic random effects probit models, we provide evidence of a strong and persistent regional polarization in the adoption and deployment of digital skills. Further, we investigate whether European Funds (European Regional Development Fund, Cohesion Funds, and European Social Funds) are capable to shape the digitalization process and to favor regional convergence.
Keywords: O14; O30; O38; 330; Digital transition; Skills; Labour markets; Persistence; Regional development; EU policies